(untitled) (Research, Society and Development, 2022)
Nutritional care has undergone unexpected changes in the pandemic of COVID-19. The objective of this article is to describe the nutritional care of patients admitted to intensive care unit in the first fifteen months of this pandemic. This is a retrospective cohort of critically ill patients with COVID-19 admitted to a referral hospital between March/2020 to June/2021. Clinical (complaints, comorbidities, length of stay and evolution), nutritional (nutritional diagnosis and diet prescribed at admission) and patient’s origin were evaluated. The Statistical Package for the Social Sciences was used for data analysis. Categorical variables were described by simple, absolute, and relative frequency, and quantitative variables by mean and standard deviation or median and interquartile range. We studied 643 patients with a mean (standard deviation) age of 63 (16) years, 374 (58.2%) were male. Hypertension was the most frequent comorbidity (61.1%), followed by diabetes mellitus (41.4%). Difficulty breathing (79.8%) and fever (48.7%) were the most frequent complaints. The median (interquartile range) hospital stay was 11 (6 - 18) days, and 570 (85.6%) patients died. Only 300 (46.7%) patients had nutritional diagnosis record, among them, 207 (69.0%) were diagnosed with overweight and 35 (11.7%) with malnutrition. There was a lack of nutritional assistance in critically ill patients with COVID-19 in the first 15 months of the pandemic. We suggest a nutritional assessment model that may contribute to better nutritional assistance in catastrophic situations, such as the one experienced in this pandemic.